Дослідження складу олійної фази косметичних засобів - Радзієвська, Ірина Гіронтіївна; Полонська, Тетяна Анатоліївна (НТУ "ХПІ", 2015)
Для оптимізації складу олійної фази косметичних кремів досліджено властивості ряду косметичних олій. Розтікання та всмоктування емолентів шкірою визначали методом Зейдлера як розповсюдження речовини по поверхні за одиницю часу. Через комплексну дію суміші трьох емолентів шкіра залишається гладкою довше, ніж при нанесенні дво- або монокомпонентної основи. Запропоновано середній склад жирової фази косметичного засобу як співвідношення трьох груп емолентов 1: 2: 1.

To establish the optimal composition of the oil phase of cosmetic creams investigated the properties of traditional cosmetic oils. In the emulsion creams oils act as emollients - substances contained in the skin, changing its appearance, soften and nourish. The most important quality criterion emollients - their spreading and skin absorbability Zeydler as determined by spreading a substance on the surface per unit time. It is shown that the spreading of oil on the skin depends on the molecular weight, namely decreases with increasing average molecular weight triacylglycerols, and the dependence is described by line. Investigated emollients can be divided into three groups - high, medium and low leakage.
Research of oil phase composition cosmetic
Keywords: емолент; розтікання; молекулярна маса; хімічний склад; emollient; fluidity; molecular weight